2022
DOI: 10.53730/ijhs.v6ns9.12218
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar gene expression of tight junction protein in nicotine rats treated with zinc and vitamin D

Abstract: The current study aimed to investigation the role of zinc and vitamin D in modulating alveolar response of nicotine stress as a model of mammals male Wistar rats. Thirty mature males werekept at 23 ± 2 C°, randomly assigned to five equal groups and treatment for 14 days, C = Control drenched vehicle without treatment, G1 = injected with i/p nicotine 1.5 mg/ kg b.w., G2 = administrated orally of zinc 60 mg/ kgb.w., G3 = administrated orally of vitamin D 250 µg/ kg b.w., G4 = administrated orally both of zinc an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The depletion of antioxidants takes place, leading to dysfunction and harm at the cellular level [10]. The occurrence of oxidative stress in the lungs as a result of nicotine exposure has been documented in many rat models Cell membrane damage is a consequence of lipid peroxidation resulting from heightened oxidative stress, [11] [12]. According to the research conducted by [13] [14], it was found that the assessment of total antioxidant capacity and malondialdehyde (MDA) levels is widely regarded as a reliable and robust method for detecting the presence of stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The depletion of antioxidants takes place, leading to dysfunction and harm at the cellular level [10]. The occurrence of oxidative stress in the lungs as a result of nicotine exposure has been documented in many rat models Cell membrane damage is a consequence of lipid peroxidation resulting from heightened oxidative stress, [11] [12]. According to the research conducted by [13] [14], it was found that the assessment of total antioxidant capacity and malondialdehyde (MDA) levels is widely regarded as a reliable and robust method for detecting the presence of stressful conditions.…”
Section: Introductionmentioning
confidence: 99%